Absorption of carbon dioxide in the aqueous mixtures of methyldiethanolamine with three types of imidazolium-based ionic liquids - Ahmady, A.; Hashim, M.A.; Aroua, Mohamed Kheireddine (Elsevier, 2011)
The absorption of carbon dioxide in the 4mol/L aqueous solution of methyldiethanolamine (MDEA) mixed with three types of ionic liquids, 1-butyl-3-methyl-imidazolium tetrafluoroborate (bmimBF 4), 1-butyl-3-methyl-imidazolium acetate (bmimAc) and 1-butyl-3-methyl-imidazolium dicyanamide (bmimDCA) were measured as a function of temperature, CO 2 partial pressure and concentration of ionic liquids in the solution. The data for aqueous MDEA+ILs solutions were obtained for temperature, CO 2 partial pressure and ionic liquids concentrations ranging from 303 to 333K, 100 to 700kPa and 0 to 2mol/L, respectively. The CO 2 loading in all the studied mixtures decreases with an increase in temperature and increases with an increase in the CO 2 partial pressure, at a given temperature. Also, it is found that the CO 2 loading decreases significantly as the ionic liquid concentration increases, but this reduction in solutions contained bmimBF 4 was less than other types of ionic liquids.